2003
DOI: 10.1088/0953-2048/16/8/304
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of critical current density in Fe-sheathed MgB2tapes by ZrSi2, ZrB2and WSi2doping

Abstract: Fe-sheathed MgB2 tapes were prepared by the in situ powder-in-tube technique by 5 at% ZrSi2, ZrB2 and WSi2 doping, respectively. The doping effect of these compounds on the microstructure and superconducting properties of MgB2 tapes has been investigated by using x-ray diffraction, scanning electron microscope, transport measurements and dc susceptibility measurements. Compared to the undoped samples, Jc for all the doped samples were much improved; the best result in terms of Jc was achieved for ZrSi2 doping,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
2
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 21 publications
(29 reference statements)
9
44
2
5
Order By: Relevance
“…At low fields the J c values for the 10 and 15 wt % SiC doped wires are lower than those for the undoped samples at both 5 and 20 K. As it was shown in previous studies, SiC doping deteriorated J c values at low field regions. 2,13,17 According to x-ray diffraction ͑XRD͒ results ͑not shown; see, e.g., Ref. 12͒, the main impurity in studied SiC doped samples was Mg 2 Si, which increased with increasing doping level, but decreased with increasing sintering temperature.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At low fields the J c values for the 10 and 15 wt % SiC doped wires are lower than those for the undoped samples at both 5 and 20 K. As it was shown in previous studies, SiC doping deteriorated J c values at low field regions. 2,13,17 According to x-ray diffraction ͑XRD͒ results ͑not shown; see, e.g., Ref. 12͒, the main impurity in studied SiC doped samples was Mg 2 Si, which increased with increasing doping level, but decreased with increasing sintering temperature.…”
Section: Resultsmentioning
confidence: 97%
“…[7][8][9][10][11][12][13][14][15][16][17][18] However SiC doping was found to have some negative effect on J c in the low field region. The J c for SiC doped MgB 2 was lower than that for undoped MgB 2 below 4 T at 5 K and below 2.5 T at 20 K. 2,13,17 There are many applications in the low field region such as in open magnetic resonance imaging ͑MRI͒ transformers and electric cables which normally operate at around 1-3 T. Thus it is important that the enhancement of J c by SiC doping can be extended to include all the field regions. In this Letter we report the results of the improved J c of SiC doped MgB 2 wires in all fields and temperature ranges.…”
Section: Introductionmentioning
confidence: 96%
“…Many groups now fabricate MgB 2 wires [1][2][3][4][5][6][7][8][9][10][11][12][13], and PIT strands are very promising for current carrying applications. Typical present day strands incorporate Fe or Cu, with perhaps Cu-Ni or monel as an outer sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Irreversibility fields for ex situ MgB 2 tapes have been seen at Ϸ12 T for field perpendicular to the tape face 14 ͓ex situ tapes are anisotropic such that H ʈ Ϸ 1. 20 with some increases seen. Hydride-based MgB 2 powder with SiC dopants was also investigated, and seen to give B c2 values of Ϸ23 T. 21 Dou et al [7][8][9][10] showed improved high-field critical current results for SiC, and similar wires measured in this laboratory showed improvements in the apparent irreversibility field as might be extrapolated from transport results.…”
mentioning
confidence: 96%